The Role of the Church in Mobilizing Women for Sustainable Peace in the Niger Delta - Olusakin, Vincent A.; Paul, Sampson; Mpigi, Goka M. (NIU Journal of Social Sciences; Vol 11 No 2 (2025): NIU Journal of Social Sciences, Vol. 11 No. 2, June 2025, 2025)
The paper explores the role of the church in mobilizing women to promote sustainable peace in the Niger Delta region. Its aims are to investigate the roles women play towards peace building and discuss how the church can effectively mobilize them towards sustaining peace. The data for this paper are based on secondary sources, while it is examined through the lens of Feminist Peace Theory.  It was discovered that the women contribute to peace through prayer for peace, peaceful protests, formation of women groups and organizations and by discouraging their husbands and sons from taking part in conflicts. It was also discovered that the church in the Niger Delta can mobilize women through rereading of Biblical texts on gender; faith-based peacebuilding; women education and healthcare system; encouraging women organizations in the Church to be involved in peace building, and organization of programmes and outreaches for women. Others are: advocacy for women’s rights and interest; encouragement of women’s active participation in politics; reintegration of female combatants and victims of conflicts into society; promotion of gender equality and campaign against root causes of conflict. The study concludes that the church's focus on mobilizing women for sustainable peace is essential for addressing the complex challenges facing the Niger Delta region. The study recommends among others, that government should provide resources and support for church-led peacebuilding initiatives by encouraging and supporting women's participation in peace processes and decision-making and encourage increase in women’s participation in politics as well as ensuring gender equality in the society and in all government appointments. Keywords: Church, Women, Peace, Peacebuilding, Niger Delta